2022
DOI: 10.1590/0034-7167-2021-0163
|View full text |Cite
|
Sign up to set email alerts
|

Reasons assigned to suicide attempts: adolescents’ perceptions

Abstract: Objective: identify the reasons for attempting suicide from the perspective of adolescents. Methods: qualitative study conducted with ten adolescents who attempted suicide and were attending a Centro de Atenção Psicossocial Infanto-Juvenil located in a city in the south of Brazil. Semi-structured interviews were held in July 2020 using WhatsApp. Data were analyzed according to Minayo’s Content Thematic Analysis. Results: the adolescents’ reports listed the reasons that triggered suicide attempts, such as cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
7
0
5
Order By: Relevance
“…This study illustrates the triple taboo (23) that permeates among professionals. It is worth mentioning that adolescents intrinsically distance themselves from the health service, either due to personal phenomena or due to the low implementation of public policies in this age group, and when SA occurs, due to the negative professional social representation, they may feel "a burden", have their assistance harassed, increasingly distance themselves from assistance (10,12) , accumulate psychic suffering and be exposed to new SA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study illustrates the triple taboo (23) that permeates among professionals. It is worth mentioning that adolescents intrinsically distance themselves from the health service, either due to personal phenomena or due to the low implementation of public policies in this age group, and when SA occurs, due to the negative professional social representation, they may feel "a burden", have their assistance harassed, increasingly distance themselves from assistance (10,12) , accumulate psychic suffering and be exposed to new SA.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, risk behaviors can be consolidated, with greater exposure to accidents and self-inflicted violence ( 11 ) . In a descriptive, qualitative, Brazilian study ( 12 ) , carried out in a Child Psychosocial Care Center, with 10 adolescents with a history of SA, it was observed that among the triggering reasons were: moving to another city and/or school; the fear and insecurity of making new friends; the loss of close family members; conflicting relationships and/or experiencing physical and/or psychological violence in a social and/or family environment; and difficulties in self-acceptance, factors that were accentuated in the context of the COVID-19 pandemic ( 13 ) . Faced with the challenges, they reported that suicide was seen as the only solution to problems, with the end of pain and sadness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20,21) Estudos têm demonstrado que o pensamento e comportamento suicidas têm uma forte associação negativa com o desempenho acadêmico e apontam a necessidade de programa de intervenção na prevenção de suicídio nos ambientes universitários. (22,23)…”
Section: Discussionunclassified
“…Nesse período, podem se consolidar comportamentos de risco, com maior exposição aos acidentes e à violência autoprovocada (11) . Em um estudo descritivo, qualitativo, brasileiro (12) , realizado em um Centro de Atenção Psicossocial Infantil, com 10 adolescentes com histórico de TS, observou-se que, entre os motivos desencadeadores, foram relatadas as mudanças de cidade e/ ou escola; o medo e insegurança de fazer novas amizades; a perda de familiares próximos; as relações conflituosas e/ou vivência de violência física e/ou psicológica em meio social e/ou familiar; e as dificuldades na autoaceitação, fatores que foram acentuados no contexto da pandemia de COVID-19 (13) . Diante dos desafios, relataram que o suicídio era visto como a única solução para os problemas, com a finalização da dor e tristeza.…”
Section: Introductionunclassified